Prognostic significance of serum potassium in patients hospitalized for acute heart failure. (11th May 2022) - Lombardi, Carlo Mario; Carubelli, Valentina; Peveri, Giulia; Inciardi, Riccardo Maria; Pagnesi, Matteo; Ravera, Alice; Tomasoni, Daniela; Garafa, Emirena; Oriecuia, Chiara; Specchia, Claudia; Metra, Marco
Abstract: Aim: We investigated the prognostic significance of serum potassium abnormalities at discharge in patients hospitalized for acute heart failure (AHF). Methods and results: In a retrospective analysis, we included 926 patients hospitalized for AHF, stratified by serum potassium levels at discharge as hypokalaemia (<3.5 mEq/L), normokalaemia (3.5–5.0 mEq/L), and hyperkalaemia (>5.0 mEq/L). The primary endpoint was all‐cause death at 1 year since hospital discharge. At discharge, 40 patients had hypokalaemia (4.3%), 840 normokalaemia (90.7%), and 46 hyperkalaemia (5.0%). Patients with hyperkalaemia at discharge were more frequently men, had more signs of congestion, and lower LVEF while patients with hypokalaemia were more likely to be women with HFpEF. Treatment with ACEi/ARBs and MRAs ≥50% of target dose at discharge was similar across groups. One year all‐cause death occurred in 10% of the patients with hypokalaemia, 13.9% of those with normokalaemia, and 30.4% of those with hyperkalaemia ( P  = 0.006). After adjustment for covariates, including renal function, background treatment, and baseline potassium level, hyperkalaemia resulted an independent predictor of the primary endpoint (HR 1.96, 95% IC [1.01–3.82]; P  = 0.048). Conclusions: In patients with AHF, the presence of hyperkalaemia at discharge is an independent predictor of 1 year all‐cause death.